DESAIN E-LEARNING PADA TAYANGAN PROGRAM BELAJAR DARI RUMAH MATA PELAJARAN BAHASA INDONESIA UNTUK SD DI TVRI - Giati Anisah (Pendidikan Agama Islam, 2020)
This research is to describe the e-learning design of the Home Learning Program in Indonesian for elementary schools aired on TVRI. The main focus into five sub-focuses, namely on learning indicators, a series of lessons, learning methods, delivery strategies, and evaluation strategies. This research is descriptive qualitative research. Data were collected using observation sheets. Learning indicators are composed of C1 and C2 competencies adjusted to the level of student intellectual development. The learning series was arranged based on a prerequisite method or prerequisite and sequentially connected. The learning method used is an expositive method that emphasizes the aspects of absorbing new information. The delivery strategy through TVRI is the right choice because it can be accessed by all students in Indonesia, both signal and operational. Evaluation cannot be carried out optimally, especially for competencies that require practice because students cannot interact with students directly